Anti-SARS-CoV-2 Antibody Screening in Healthcare Workers and Its Correlation with Clinical Presentation in Tertiary Care Hospital, Kathmandu, Nepal, from November 2020 to January 2021 - Aryal, Suraj; Pandit, Sanskriti; Pokhrel, Sushant; Chhusyabaga, Mandira; Bista, Pabitra; Bhatt, Mahendra Psd.; Subedi, Dharma Datta; Rijal, Basista Psd. (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Background. Antibody titer and the life span of antibodies against SARS-CoV-2 have been found to be associated with the clinical presentation in individuals. The extent of exposure of healthcare workers and the general public to SARS-CoV-2 needs to be assessed to monitor the COVID-19 pandemic. Thus, this study is an attempt in assessing the anti-SARS-CoV-2 antibody in health care workers. Methods. This laboratory-based cross-sectional study was performed in Manmohan Memorial Medical College and Teaching Hospital, Kathmandu from November 2020 to January 2021. A total of 185 HCWs were enrolled in this study. Their serum samples were screened for anti-SARS-CoV-2 antibodies, and a structured questionnaire was administered to collect further information. Anti-SARS-CoV-2 antibody screening was performed using lateral flow immunoassay. The data were analyzed using SPSS version 20. Results. Among 185 HCWs that participated in the study, 41 (22.2%) tested positive for the anti-SARS-CoV-2 antibody. Of these 41 HCWs, 37 tested positive for IgG only and 4 of them tested positive for both IgM and IgG antibodies. The presence of the previous history of SARS-CoV-2 infection (p<0.001), the presence of flu-like symptoms within the last 6 months (p<0.001), and the presence of positive contact history (p=0.002) were statistically significant with the presence of the antibody among HCWs. Conclusion. Healthcare workers carry a high burden of SARS-CoV-2 infection and are at risk of acquiring infection from their workplace. Anti-SARS-CoV-2 antibody screening among healthcare workers is highly recommended in multiple healthcare settings as it can help in monitoring transmission dynamics and evaluation of infection control policies.